The Selection of PPP Type Through Value for Money Analysis: A Case Study of Jakarta-Surabaya Railway Project - Purnomo, Dwi Agus; Yulianta, Yulianta; Utomo, Djoko Prijo; Sucipto, Sucipto (UI Scholars Hub, 2020)
With the suboptimal performance of the Jakarta-Surabaya corridor railway currently operating, the Government of Indonesia intends to upgrade the railway system in terms of speed performance as well as to engage the participation of both the public and private sectors in the upgrading project as mandated in Presidential Regulation Number 38/2015. Through this research, the type selection of the Public-Private Partnership (PPP) scheme and their implications on the Jakarta-Surabaya railway project will be demonstrated by conducting analysis to the alternative scenarios of the study on railway technology selection with an emphasis on economic and financial feasibility aspects to determine the suitable PPP type, which is validated through Value for Money (VfM) analysis, where the benefits of the selected PPP type in terms of economic, financial, and non-financial aspects were examined through numerical tests, the result of which indicated that with the VfM value of the actual data of IDR 224.51 trillion, and the most significant changes in VfM value for each variable change are in the 20-year concession period which reduces the VfM value by 4%. Of all the variable changes, there is no minus VfM value, indicating that public projects are in an improved condition with the PPP scheme.